Inhibition of FGF Signalling Pathway Augments the Expression of Pluripotency and Trophoblast Lineage Marker Genes in Porcine Parthenogenetic Blastocyst. (13th July 2016) - Li, LY; Li, MM; Yang, SF; Zhang, J; Li, Z; Zhang, H; Zhu, L; Zhu, X; Verma, V; Liu, Q; Shi, D; Huang, B
Contents: The consistent failure to isolate bona fide pluripotent cell lines from livestock indicates that the underlying mechanisms of early lineage specification are poorly defined. Unlike other species, the contrivances of segregation have been comprehensively studied in the mouse. In mouse, FGF/MAPK signalling pathway dictates the segregation of hypoblast (primitive endoderm). However, it is not evident whether this mechanism is also conserved in livestock. Here, in this study, we examined the roles of FGF/MAP kinase signalling pathways in porcine parthenogenetic embryos during the early development. Porcine parthenogenetic embryos were cultured in the medium addition with FGFR inhibitor BGJ398 (10 μm ) or DEMOS. Pluripotency‐ and lineage‐related gene expressions in the early porcine embryos were determined. Compared to control, total cell numbers on day 7 were significantly higher (55 ± 5.96 vs 47 ± 1.97, p < 0.05) in embryos cultured in the presence of BGJ398, but had no significant effect on the rate of blastocyst development (47% vs 44%, p > 0.05). Nonetheless, BGJ398 treatment significantly augmented the expression of pluripotency and trophoblast marker genes ( SOX2, OCT4, KLF4 and CDX2 ), but did not significantly change the expression of NANOG and hypoblast marker gene ( GATA4 ). Furthermore, the addition of FGF signalling agonist (FGF2) during the embryo development significantly decreased the expression of pluripotency and trophoblast marker genes ( SOX2, NANOG, KLF4 and CDX2 ), but no significant effect on the expression of OCT4 and GATA4 was observed. Here, we exhibit that inhibition of FGF signalling could improve the quality of the porcine embryo and escalate the chance to capture pluripotency. Besides, it also promotes the trophoblast development of porcine parthenogenetic embryo. In addition, the data suggested that FGF signalling pathway is dispensable for the segregation of hypoblast and epiblast lineages in porcine embryo during the early development.